Frequency Efficiency Evaluation of Query Airspace Surveillance Systems - Старокожев, С. В.; Ткач, М. Г.; Глущенко, А. О.; Даценко, О. О.; Чернишов, М. В.; Чумак, В. С. (PIC S&T, 2021)
In this work, there was carried out an evaluation of frequency efficiency of both the interrogation signal channel and the response signal channel in case of intra-system and intentional (correlated and uncorrelated), as well as fluctuation interference. The evaluation based on the representation of interrogation radar systems for observing airspace in the form of two-channel systems for transmitting information of interrogation signals and response signals. It is shown that the use of interrogation signals and response signals in the form of an interval-time and positional code leads to the need for a significant receiving path bandwidth expansion of both the aircraft transponder and the interrogating radar system as a whole. This caused by the requirements for obtaining sharp edges of the received signals, which is necessary for decoding them and leads to a significant decrease in the frequency efficiency of the considered information systems and, as a consequence, to a decrease in the noise immunity of both the request channel and the response channel of the considered information systems.
Keywords: Airspace control systems; Secondary Surveillance Radar; Identification Friend or Foe; air traffic control; request signal